Educational nurse‐led lifestyle intervention for persons with mental illness. (24th November 2017) - Rönngren, Ylva; Björk, Annette; Audulv, Åsa; Enmarker, Ingela; Kristiansen, Lisbeth; Haage, David
Abstract: Although persons with severe mental illness face an increased risk of mortality and of developing negative health outcomes, research has shown that lifestyle interventions can sufficiently support their health. In response, this study examined a nurse‐led lifestyle intervention developed in cooperation with members of municipal and county councils to gauge its impact on the quality of life, cognitive performance, walking capacity, and body composition of persons with severe mental illness. Lasting 26 weeks and involving 38 persons with severe mental illness, the intervention prioritised two components: the interpersonal relationships of persons with severe mental illness, staff, and group leaders and group education about physical and mental health. Pre–post intervention measurements of quality of life collected with the Manchester Short Assessment of Quality of Life, cognitive performance with the Frontal Systems Behaviour Scale, walking capacity with a 6‐min walk test, and body composition in terms of waist circumference and body mass index were analysed using a nonparametric test Wilcoxon signed‐rank test. Results suggest that the intervention afforded significant improvements in the health‐related variables of quality of life, cognitive performance, walking capacity, and waist circumference for persons with severe mental illness. However, long‐term studies with control groups and that examine parameters related to cardiovascular risk factors are essential to ensure the sustained impact of the intervention.